A generalized model for predicting stress distributions in thick adhesive joints using a higher-order displacement approach. (1st July 2022) - Methfessel, T.S.; Becker, W.
Abstract: As typical elements in lightweight applications, adhesive bonds bring many practical advantages over other joining technologies, such as their high strength-to-weight ratio, their damage-free joining process, and an over a wide area distributed load introduction into the adhesive layer. When modeling bonded joints for stress analysis or failure prediction, the adhesive layer is usually simplified to an interface, as it is very thin compared to the parts being joined. However, for thicker adhesive layers, these models no longer succeed in accurately predicting the stresses that occur, as many simplifications no longer apply. Therefore, we present a model that considers the adhesive layer as a continuum rather than an interface. Unlike previous works, we apply general energy principles enabling the determination of stresses as well as displacements throughout the adhesive layer with improved accuracy. A new, extended displacement approach with terms of higher order enables the capture of complex deformation effects that occur in thick adhesive layers. The new model is valid for various joint shapes, load cases, and material configurations and enables a quick, analytical prediction of stress and deformation distributions in the adhesive layer. For validation, we compare the results with those of previous models and finite element calculations.